Comparing three‐dimensional models of placenta accreta spectrum with surgical findings. Issue 1 (16th June 2021) - Mulligan, Karen M.; Bartels, Helena C.; Armstrong, Fionnvola; Immel, Erwin; Corcoran, Siobhan; Walsh, Jennifer M.; McAuliffe, Fionnuala; McParland, Peter; Carroll, Stephen; Higgins, Shane; Mahony, Rhona; Donnelly, Jennifer; et al.
Abstract: Objective: Placenta accreta spectrum (PAS) is associated with significant maternal morbidity mainly related to blood loss. Pre‐operative planning is aided by antenatal ultrasound and magnetic resonance imaging. We sought to assess whether three‐dimensional (3D) models from MR images were accurate when compared with surgical and pathological findings. Methods: Digital Imaging and Communications in Medicine files containing MR images with varying severity of PAS ( n  = 4) were modeled using 3D Slicer . Placenta, bladder, and myometrial defects were modeled. Myometrial defects at three different uterine locations were included—anterior, lateral and inferior. 3D models were used to identify the relationship between the myometrial defect and the internal cervical os. Findings were validated in a larger series of PAS cases ( n  = 14) where patterns of invasion were compared with estimated blood loss and distance from defect to the internal os. Results: The defect illustrated in the four 3D models correlates to both surgical and pathological findings in terms of depth and pattern of invasion, location of defect, bladder involvement. Blood loss and topography of the defect from 3D modeling were examined in 14 further cases. Inferior defects were associated with increased blood loss compared with anterior defects. Increased distance from cervix was associated with reduced blood loss ( R 2  = 0.352, P  = 0.01). Conclusion: Three‐dimensional models of PAS provide an accurate preoperative description of placental invasion and should be investigated as a tool for selecting patients for uterine‐conserving surgery. Accurate 3D models of placenta accreta spectrum are achievable and may provide additional information, such as distance of the defect from the internal os. Abstract : Accurate 3D models of placenta accreta spectrum are achievable and may provide additional information, such as distance from the defect to the internal cervical os.